The Saudi Arabian-Iranian Relations and the Security Dilemma - Παπασταμοπούλου, Χριστίνα (Πανεπιστήμιο Πελοποννήσου, 2023)
After the Iranian Revolution in 1979, the relations between Saudi Arabia and Iran have been hostile. Both their conflicted geopolitical interests and sectarianism have triggered this very hostility. The two states are used to playing a “balance of power game”, which may easily lead them to an escalation of the conflict. More particularly, Saudi Arabia and Iran have been competing with each other to expand their spheres of influence either in the Gulf region or in the wider Middle East and North Africa. So far, Saudi Arabia and Iran have participated in proxy wars in the region. Nevertheless, nowadays, this competition has been moderated due to negotiations taking place after a Chinese initiative. In the current assignment, we will examine the developments of their relations from the Iranian Revolution (1979) up to the signing of the “Joint Trilateral Cooperation Agreement” (2023). Based on the theoretical approach of realism, we will try to answer the question whether there is a security dilemma between the two states. After thorough analysis, we will conclude that there is actually a security dilemma between them which has, nowadays, been moderated after a Chinese initiative.
Οι σχέσεις μεταξύ Σαουδικής Αραβίας και Ιράν και το δίλημμα ασφαλείας
Keywords: Σαουδική Αραβία--Εξωτερικές σχέσεις--Ιράν; Ιράν--Εξωτερικές σχέσεις--Σαουδική Αραβία; Σαουδική Αραβία; Ιράν; Ασφάλεια